Conformational analysis and global warming potentials of 1, 1, 1, 2, 3, 3-hexafluoropropane and 1, 1, 2, 2, 3-pentafluoropropane from absorption spectroscopy. (March 2019) - Godin, Paul J.; Johnson, Hayden; Piunno, Romina; Le Bris, Karine; Strong, Kimberly
Highlights: Cross-sections of 1, 1, 1, 2, 3, 3-hexafluoropropane (HFC-236ea) and 1, 1, 2, 2, 3-pentafluoropropane (HFC-245ca) were measured from 550 to 3400 cm − 1 for a temperature range of 300–362 K. Good agreement between new results, prior data, and density functional theory (DFT). Radiative efficiency and global warming potential are calculated using a combination of DFT and experimental spectra to obtain a wider spectral range than previous calculations. Abstract: Absorption cross-sections of 1, 1, 1, 2, 3, 3-hexafluoropropane (HFC-236ea) and 1, 1, 2, 2, 3-pentafluoropropane (HFC-245ca) were derived from Fourier transform infrared spectra recorded from 550 to 3400 cm − 1 with a resolution of 0.1 cm − 1 over a temperature range of 300–365 K. Good agreement was found between the experimentally derived results, theoretical spectra from density functional theory (DFT) calculations, and previously published experimental measurements. The only temperature dependence observed was in the amplitude of some of the absorption peaks due to the changing ratio of the stable conformations of both molecules studied. This temperature dependence does not result in a significant trend in integrated band strength as a function of temperature. The average value for the integrated band strength of HFC-236ea was found to be (1.982 ± 0.012)x10 − 16 cm molecule − 1 over the spectral range of 550 to 3026 cm − 1 . The average value for the integrated band strength of HFC-245ca was found to be (1.348 ± 0.35)x10 − 16 cm molecule − 1 over the spectral range of 570 to 3035 cm − 1 . Radiative efficiency (RE) and the global warming potential (GWP) for both molecules were also derived, accounting for corrections due to atmospheric lifetimes and stratospheric temperature adjustment. A RE of 0.256 ± 0.034 Wm − 2 ppbv − 1 was obtained for HFC-236ea, which leads to a GWP100 of 1141 ± 402 for 550–3000 cm − 1 . For HFC-245ca, a RE of 0.197 ± 0.023 Wm − 2 ppbv − 1 was derived, which leads to a GWP100 of 588 ± 205 for 550–3000 cm − 1 . The DFT calculation was linearly adjusted to match the experimental spectrum. Using this adjusted DFT spectrum to expand the range below 550 to 0 cm − 1 increases the RE to 0.265 ± 0.035 Wm − 2 ppbv − 1 and the GWP100 to 1181 ± 417 for HFC-236ea; while for HFC-245ca, the RE increases to 0.202 ± 0.027 Wm − 2 ppbv − 1 and the GWP100 to 602 ± 210.